Single-dose pharmacokinetics of BMS-986177/JNJ-70033093 in participants with mild or moderate hepatic impairment compared to healthy participants. (25th November 2020) - Perera, V; Abelian, G; Li, D; Wang, Z; Zhang, L; Lubin, S; Wang, J; Bello, A; Murthy, B
Abstract: Background: According to the scientific evidence accumulated to date (ie, genetic, epidemiological, preclinical, clinical), the modulation of Factor XI (FXI) function may provide a novel mechanism for systemic anticoagulation without increasing the risk of clinically significant bleeding in a variety of conditions predisposing patients to a high risk of thrombotic or bleeding events. BMS-986177/JNJ-70033093 (BMS-177/JNJ-3093) is a small molecule that inhibits the active form of FXI (FXIa) with high affinity and selectivity. Depending on the indication, BMS-177/JNJ-3093 may provide benefit to patients as add-on or potentially replacement therapy to the current standard of care antithrombotic agents. Patients with hepatic impairment may have an increased risk of bleeding when using existing antithrombotic agents and therefore may benefit from drugs with an improved safety profile. Purpose: To assess the effect of mild or moderate hepatic impairment on the pharmacokinetic (PK) properties of BMS-177/JNJ-3093. Methods: This was a multicenter, open-label, non-randomized, single-dose study. A single 60-mg oral dose of BMS-177/JNJ-3093 was administered to 9 participants with mild hepatic impairment (Child-Pugh class A), 8 participants with moderate hepatic impairment (Child-Pugh class B), and 9 healthy participants with normal hepatic function. Healthy participants were matched to participants with hepatic impairment in each Child-Pugh class with regard to body weight. To assess the effects of hepatic impairment on BMS-177/JNJ-3093 PK, an analysis of variance was performed on the natural log-transformed Cmax, AUC(INF), and AUC(0-T) with hepatic function group as a fixed effect. Results: BMS-177/JNJ-3093 was well tolerated when administered as an oral dose of 60 mg in participants with mild or moderate hepatic impairment and healthy participants with normal hepatic function. There were no deaths, serious adverse events (AEs), severe AEs, bleeding AEs, or discontinuations due to an AE reported during the study. The geometric mean ratios (GMRs) (90% CI) comparing mild hepatic impairment to normal hepatic function were 1.180 (0.735, 1.895) and 1.168 (0.725, 1.882) for total BMS-177/JNJ-3093 maximum concentration (Cmax) and area under the curve from time 0 to infinity (AUC(INF)), respectively. The GMRs (90% CI) comparing moderate hepatic impairment to normal hepatic function were 1.140 (0.699, 1.857) and 0.996 (0.609, 1.628) for total BMS-177/JNJ-3093 Cmax and AUC(INF), respectively. Overall, levels of activated partial thromboplastin time (aPTT) increased in an exposure-related manner following single oral doses of 60 mg BMS-177/JNJ-3093 in all groups. Conclusion: BMS-177/JNJ-3093 was well tolerated in the normal healthy participants and those with mild or moderate hepatic impairment. The observed changes indicate that a dose adjustment in these populations may not be necessary. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): This work was sponsored by Bristol-Myers Squibb and Janssen Research & Development, LLC